On-site full-scale tests of a timber queen-post truss - Branco, Jorge M. (2018)
On-site tests were performed on an existing traditional timber truss. The main goal of the tests was to evaluate the overall behavior of the timber truss under symmetric and non-symmetric vertical loading. Moreover, the influence of the location of the point loads application was assessed, with and without eccentricity relatively to the joints. The loading tests were preceded by a visual and non-destructive inspection aimed at collecting geometric data and assessing the level of decay of each member. The field tests results of a queen-post truss are presented and analyzed. A numerical model was developed to reproduce and analyze the test results.